Successful liver transplant from a hemophilia A donor with no development of hemophilia A in recipient. (9th March 2020) - Kurian, Christine J.; Drelich, Douglass A.; Rizk, Sanaa
Abstract: Background: Hemophilia A is an X‐linked inherited bleeding disorder caused by deficiency of coagulation factor VIII. Factor VIII is activated as part of the intrinsic coagulation cascade. It plays a crucial role as the cofactor in the intrinsic "tenase" complex activating factor X to assist in clot formation. Absence or mutation of this coagulation factor leads to excessive bleeding. Clinical manifestations of hemophilia relate to bleeding from impaired hemostasis, sequelae from bleeding, or complications of coagulation factor infusion. Diagnostic criteria for Hemophilia A include factor VIII activity level below 40% of normal, presence of a mutated F8 gene, and the absence of von Willebrand disease ( F8 gene ‐ Genetics Home Reference ‐ NIH. https://ghr.nlm.nih.gov/gene/F8 ). Patients who have this intrinsic defect in the coagulation cascade have a characteristically prolonged PTT. It is theorized that the majority of factor VIII is synthesized mainly in the liver, by way of liver sinusoidal endothelial cells (Arruda VR. Haematologica . 2015;100(7):849–850). Extrahepatic production also occurs in the endothelial cells, kidneys, and lymphatic tissue. In 1969, Marchioro et al showed that transplantation of normal liver to hemophilia dog could normalize plasma factor VIII levels (Marchioro T L, Science . 1969;163(3863):188–190). These results were subsequently proven in humans. Liver transplantation from hemophilia A donors without factor VIII inhibitor is not commonly performed due to the perceived risk of developing hemophilia A in the recipient. There is currently limited literature aimed at elucidating this risk. We present a case of liver transplantation in a hemophilia A donor to a recipient with no history of hemophilia A with literature reviewis a case report, objective and method do not apply. Objective and method: We did a case report and literature review of a liver transplant receipient fro ma hemohpila A donor. Results: The receipient of the liver from hemophilia A donor did not develop hemophilia post transplant and had normal factor VIII levels. conclusion: To our knowledge, this is only the second case in humans of hemophilia A patient as a donor in liver transplantation. As the indications for liver transplantation have expanded, there is a need to expand the donor list, and possibly not exclude this population as viable donor option.